Advanced myocardial characterization and function with cardiac CT - Lisi, Costanza; Moser, Lukas J.; Mergen, Victor; Klambauer, Konstantin; Uçar, Eda; Eberhard, Matthias; Alkadhi, Hatem (The international journal of cardiovascular imaging, 2024)
Non-invasive imaging with characterization and quantification of the myocardium with computed tomography (CT) became feasible owing to recent technical developments in CT technology. Cardiac CT can serve as an alternative modality when cardiac magnetic resonance imaging and/or echocardiography are contraindicated, not feasible, inconclusive, or non-diagnostic. This review summarizes the current and potential future role of cardiac CT for myocardial characterization including a summary of late enhancement techniques, extracellular volume quantification, and strain analysis. In addition, this review highlights potential fields for research about myocardial characterization with CT to possibly include it in clinical routine in the future. Graphical Abstract Cardiac computed tomography as an increasingly important alternative for myocardial tissue characterization and functional assessment.